PENINGKATAN KETAHANAN AUS BAJA KARBON RENDAH MELALUI VARIASI SUHU CARBURIZING - Tsamroh, Dewi Izzatus; Yazirin, Cepi; Putra, Agus Dwi (Universitas Islam Malang, 2024)
The automotive industry is one of the industries that is currently developing in Indonesia. Research has been carried out on materials used in the automotive industry, one of which is improving the mechanical properties of low carbon steel which is widely used as sprocket material. Sprockets are parts of a motorbike that require surface hardness and ductility at the core. So carburizing treatment is the right treatment to increase the wear resistance of low carbon steel. The material used in this research is ST 37. This research aims to increase the surface hardness of ST 37 by varying the carburizing temperature, where the temperatures used are 850℃ and 900℃ with a holding time of 3 hours. Wear resistance testing uses the weight loss method by comparing the ST 37 sprocket with sprockets sold on the market. The highest wear resistance was obtained on sprockets with carburizing treatment at a temperature of 900℃ with test results of 1.65 x 10-2 mm3/hour.